Suggested physical activities in developing physical fitness among the educable mentally retarded - Saplala, Lauretta Padilla (1973)
The purpose of the study is to present physical activities that will help develop physical fitness among the educable mentally retarded children. It is recommended that special education teachers should have a special physical education course in the teaching of mentally retarded children and the physical activities to be given to them should be integrated with the rest of the school program. There should likewise be available space and equipment to permit free movement, and enough time be alloted to the physical activity program to ensure adequate development. Lastly, physical activities should be suited to the mentally retarded children's level of maturation.